2008
DOI: 10.1002/adfm.200701116
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Responsive Solution Partition of Organic–Inorganic Hybrid Poly(N‐isopropylacrylamide)‐Coated Mesoporous Silica Nanospheres

Abstract: A series of poly(N‐isopropylacrylamide)‐coated mesoporous silica nanoparticle materials (PNiPAm‐MSNs) has been synthesized by a surface‐initiated living radical polymerization with a reversible addition–fragmentation chain transfer (RAFT) reaction. The structure and the degree of polymerization of the PNiPAm‐MSNs has been characterized by a variety of techniques, including nitrogen sorption analysis, 29Si and 13C solid‐state NMR spectroscopy, transmission electron microscopy (TEM), and powder X‐ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(99 citation statements)
references
References 53 publications
7
91
0
1
Order By: Relevance
“…Moreover, the surface area for samples with PNIPAM was about 740 m 2 /g (measured by nitrogen adsorption experiments), which was almost the same as that reported previously for the sample without PNIPAM (640-860 m 2 /g) [22]. Chung et al reported that the thickness of the PNIPAM layer was 19 nm when the mesoporous silica was coated with about 7 wt.% of PNIPAM [26]. Consequently, it was expected that the PNIPAM would be present as a thin layer of less than 10 nm on the external surface of the mesoporous silica.…”
Section: Structural Characterization Of (Pnipam+bis)/mesoporous Silicasupporting
confidence: 67%
“…Moreover, the surface area for samples with PNIPAM was about 740 m 2 /g (measured by nitrogen adsorption experiments), which was almost the same as that reported previously for the sample without PNIPAM (640-860 m 2 /g) [22]. Chung et al reported that the thickness of the PNIPAM layer was 19 nm when the mesoporous silica was coated with about 7 wt.% of PNIPAM [26]. Consequently, it was expected that the PNIPAM would be present as a thin layer of less than 10 nm on the external surface of the mesoporous silica.…”
Section: Structural Characterization Of (Pnipam+bis)/mesoporous Silicasupporting
confidence: 67%
“…Other researchers also investigated the PNIPAM-based thermo-responsive DDS using MSN as the drug container. [130][131][132][133][134][135][136] This new core-shell thermo-responsive nanocarrier showed promising potential in controlled drug/gene delivery.…”
Section: Thermo-responsive Drug Deliverymentioning
confidence: 99%
“…This strategy can be utilised to prepare stimuli responsive MSN based nanovalves, where drugs can be loaded inside the porous structure and released at a certain temperature. 149 Using the novel W/O pickering emulsion based technique and solid silica sphere as a stabiliser, Zhang et al prepared temperature responsive hybrid capsules made up of PNIPAm and polymethyl methacrylates (PMMA). Ibuprofen release from the composite particles was controlled by temperature and wall thickness of the polymer.…”
Section: Thermal Responsive Systemsmentioning
confidence: 99%